2020
DOI: 10.1093/neuros/nyaa272
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification and Its Clinical Significance in Spinal Schwannoma Based on the Membranous Hierarchy

Abstract: BACKGROUND Spinal schwannoma is a common benign tumor. However, the high recurrence rate and incidence of surgical complications are unsolved problems. OBJECTIVE To propose a morphological classification of spinal schwannoma based on tumor-membrane relationships to increase the gross total resection (GTR) rate and to decrease the incidence of surgical complications. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Sun et al developed a classification system for spinal schwannomas that includes tumor location and volume; however, this classification system does not contain information on patients with bone erosion or tumors located at the isolated foraminal level 1 . Xin et al created a classification system based on the membranous locations of the tumor, but this study also does not provide information about bone erosion 5 . Our series reflects the surgical results of a senior surgeon with experience in transforaminal surgery in more than 200 cases (far lateral disc herniations, spinal stenoses, different spinal tumors including schwannomas, metastases, and chordomas).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sun et al developed a classification system for spinal schwannomas that includes tumor location and volume; however, this classification system does not contain information on patients with bone erosion or tumors located at the isolated foraminal level 1 . Xin et al created a classification system based on the membranous locations of the tumor, but this study also does not provide information about bone erosion 5 . Our series reflects the surgical results of a senior surgeon with experience in transforaminal surgery in more than 200 cases (far lateral disc herniations, spinal stenoses, different spinal tumors including schwannomas, metastases, and chordomas).…”
Section: Discussionmentioning
confidence: 97%
“…Despite these advancements, preoperative planning is critical for effective treatment, and in particular, appropriate tumor categorization. Multiple classification methods for spinal schwannomas have been proposed in the literature 1,2,4,5 . Our study presents the surgical results of a senior surgeon in SSs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the publication by Xin et al 2020, the current classifications were reviewed and compared, identifying the advantages and disadvantages of the use of each one, which were summarized in one list, see table 1 for a better understanding [28].…”
Section: E Velázquez Et Al Open Journal Of Modern Neurosurgerymentioning
confidence: 99%
“…Giant Schwannomas are infrequent, however, given that most of their life they are asymptomatic when they establish clinically they have involved important structures, the direction in which they grow as well as the structures they involve and the vertebral levels they occupy will determine the complexity of the procedure for their extirpation, other surgeons and anatomists have tried to establish scales or classifications to facilitate decision making when facing them, however according to the literature review none of them has proven to be completely useful given the limitations they have demonstrated, it's not the purpose of this article to discuss the limitations of one or the other, however, Table 1 has been attached that briefly discusses them [28].…”
Section: E Velázquez Et Al Open Journal Of Modern Neurosurgerymentioning
confidence: 99%
“…The other issue is location of the tumors in relation to the surrounding structures. Xin et al [ 3 ], demonstrated a novel classification of the schwannoma based on the membranous structures including the dura matter, the arachnoid, and the pia matter. The margins between the tumors and the surrounding structures would define the surgical dissection planes.…”
mentioning
confidence: 99%